Commonsense Spatial Reasoning: an Informational Perspective - Stefania Bandini; Gianluca Colombo; Alessandro Mosca; Matteo Palmonari (tripleC: Communication, Capitalism & Critique)
Pervasive Computing systems are characterized by possibly mobile components distributed in the environment and are devoted to collect, process and manage information in order to support users in different kind of activities. High-level correlation of information in such context can be defined, exploiting a formal model arising from the spatial disposition of information sources, as a form of commonsense spatial reasoning. With respect to this model, a Hybrid Logic to formalize commonsense spatial reasoning in these context has been defined. Here, on the basis of relevant analogies among Pervasive Computing and human practice in handling spatial knowledge, we suggest to provide the term “commonsense” with a positive meaning, showing that our logical framework captures some features of non-mathematical reasoning when spatially qualified information is concerned. The focus on such features and the analogies mentioned above suggest to qualify our approach to (commonsense) spatial reasoning as an informational approach.